PWE-192 Helicobacter eradication aspirin trial (Heat): side effects analysis of mid-trial data. (22nd June 2015) - Wright, K; Ho, WH; Hawkey, CJ; Smith, MD; Dumbleton, JS
Abstract : Introduction: HEAT is a large multicentre trial involving patients aged 60+ years, on low dose aspirin, breath-tested positive to H.pylori and randomised either to 1-week triple therapy H. pylori eradication or placebo. Triple therapy consists of lansoprazole 30mg, clarithromycin 500mg and metronidazole 400mg, twice daily. We conducted a side effects analysis of mid-trial HEAT data, gathered over an approximate 2.5 year period. Method: A HEAT side effect report includes 3 pieces of information – name, severity (1=mild, 2=moderate, 3=severe), duration in days – with patient's allowed to report up to 6 side effect episodes. We analyse these data using descriptive statistics. In addition, for the subgroup experiencing a side effect, we score each episode, formed as the product of severity by duration. Then, for each patient, we aggregate episode scores to generate a total side effect score; a measure that is increasing in both severity and duration. We model the total score using regression methods, controlling for patient characteristics. Results: Of all 1213 patients, 45.34% (550) reported at least one treatment side effect. As we are currently blind to randomisation, assuming all who report a side effect are in the active treatment arm, the incident rate of 90.7% (550 of 1213/2) differs considerably from the 19.7% rate reported in Bazzoli et al . 1 for a trial arm with a similar dosage triple therapy regimen, although their cohort, with an average age of 52 years, is considerably younger than that of HEAT (average 73 years). The Table 1 gives the count of patient's reporting multiple episodes categorised by severity: Diarrhoea is the most frequently reported side effect with a total of 205 episodes reported by 102 patients, with multiple reports recorded by 24 patients; 30 episodes were reported to be severe. Diarrhoea episode duration averages 3.9 days (range 1–14 days). Linear regression of the total side effects score (n = 543, mean = 18.7, stddev = 22.3, min = 1, max = 180) found no statistically significant systematic dependence of the score on patient characteristics, apart from gender (beta=3.4, p = 0.005), in which women are more likely than men to return a higher score. Conclusion: To mid-trial, the side effects profile experienced by HEAT participants spans the list of those that are expected, with diarrhoea the most common. It is encouraging that there appears to be no systematic pattern of patient characteristics affecting side effects, although women experience significantly greater impacts than do men. Disclosure of interest: None Declared. Reference: Bazzoli F, et al . Aliment Pharmacol Ther. 2002;16:153–158.